Klaster Pertumbuhan Kultur Tunas Talas (Colocasia esculenta (L.) Schot.) cv. Bentul Tetraploid Berdasarkan Metode Ward - Wulansari, Aida; Martin, Andri Fadillah; Ermayanti, Tri Muji (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTTaro (Colocasia esculenta (L.) Schot.) has been cultivated for a long time in Indonesia. Taro tuber can be used as alternative food for rice substitute to support food diversification program. Taro cv. Bentul is preferable to farmers because it has few buds that are easy to maintain and adaptable in both lowlands and highlands. Its tuber has a delicious taste and a soft texture. Somatic cell manipulation of Indonesian taro through biotechnology may contribute to increase its productivity. One of in vitro technique for somatic cell manipulation is polyploidy. Oryzalin has been able to obtain taro cv. Bentul tetraploid. A total of 17 tetraploid clones were used in this study for clustering. Those clones were obtained from previous research and have stable ploidy level. The objective of this study was to determine cluster Bentul tetraploid of shoot culture using Ward method based on their in vitro growth as an initial selection before further selection in the field. Shoot tips of tetraploid were cultured on MS medium containing 2 mg/l BAP, 1 mg/l thiamine and 2 mg/l adenine for 6 weeks. The observed growth variables were number of shoots, length of petiole, number of leaves and roots. The clusterring was done using Ward and Euclidean Distance method followed by Analysis of Varians and Duncan Multiple Range Tests (DMRT). Out of 17 clones observed resulted in 3 clusters. Cluster 1 consisted of 2 clones, cluster 2 consisted of 9 clones, and cluster 3 consisted of 6 clones respectively. The best cluster was cluster 3 which was significantly different on the average number of shoots and leaves. Cluster 3 was dominated by clones derived from oryzalin at 75 ?M.Keywords: taro (Colocasia esculenta (L.) Schot.), tetraploid, in vitro growth, cluster analysis, Ward